FlowMaster: A Gamified Media Based on Discovery Learning for Developing Critical Thinking Skills on the Concept of Dynamic Fluids - Imam Akmal Sadad; Joko Budi Porenomo Joko; Hartono Hartono (Universitas Negeri Semarang, 2026)
This study aims to develop FlowMaster, a gamified instructional media based on discovery learning, designed to enhance students' critical thinking skills in the context of Dynamic Fluids. The research adopts an R&D (Research and Development) approach utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved 60 eleventh-grade science students from SMA Negeri 9 Semarang, divided into an experimental group (using FlowMaster) and a control group (using conventional media). Expert validation results indicated a very high level of feasibility for the media aspect (93.33%) and a high feasibility for the content aspect (81.11%). Effectiveness testing employed a quasi-experimental design, revealing a significant improvement in critical thinking skills within the experimental group (N-Gain = 0.779; categorized as high), outperforming the control group (N-Gain = 0.659). Analysis of critical thinking indicators showed that FlowMaster was most effective in enhancing decision-making skills (N-Gain = 0.78) and the ability to provide simple explanations (N-Gain = 0.85), supported by gamification features such as Discovery Missions and interactive simulations. These findings demonstrate that integrating gamification with discovery learning through FlutterFlow-based media offers an innovative solution for fostering students’ cognitive engagement, aligned with the demands of 21st-century education.